DESHA VIRUDDHA IN DIFFERENT REGIONS OF INDIA (International Journal of Ayurveda and Pharma Research, 2015)
Ayuveda is blended with lots of Siddhantas. Among them Viruddhahara is one of the most imperative and well-known Siddhant. In Viruddhahara, Samyoga-viruddha and Virya-viruddha are the most familiar and emphasized frequently. Rests of the Viruddhas are remain untouched or not highlighted to that extend. Man has natural tendency towards change in the life at every stage hence the food and food habits are also covered by this tendency. Although some groceries are precise to specific region and people take that foodstuffs unknowing which may not be good for an individual health. These kinds of food one can be included in Desha-viruddha.As every state is having different regional diversity and also the diversity of their food habits, hence it is very difficult to conclude Desha Viruddha according to intake of foodstuff at regular base. But then also the efforts have been put here to state various Desha Viruddha according to various regions along with their mode of action.